Thermobiology and Clinical Application of Interstitial and Superficial Hyperthermia in Two Groups of Patients: a New Approach for Treating Malignant Tumors - Maesadjie Tjokronagoro, Maesadjie Tjokronagoro (Universitas Gadjah Mada, 1989)
Two groups of patients were treated with combined modality radiation and hyperthermia at the Strahlentherapeutische Klinik, Universitit Erlangen-Nurnberg, Federal Republic of Germany, from October 1987 to July 1988. The first group of 8 patients (4 cases of carcinoma of-the floor of the mouth, 3 cases of tongue carcinoma, 1 case of Ewing sarcoma) was treated with combination radiation and interstitial hyperthermia. 7 cases have complete remission (87.5%), whereas 1 case has partial remission (12.5%). The second group of 6 patients (5 breast cancer recurrences in the chest wall and supraclavicular region, 1 case with cancer of the parotid gland) were treated with combined radiation of electron beam 12 Mev by Siemens Mevatron 20 and superficial hyperthermia using Lund Buehler hyperthermia system 4010, 915 MHZ/20 W, once a week. 4 cases have complete remission (66.6%) and two cases have partial remission (33.3%). As a background of hyperthermia we also describe the principles of thermobiology, heat interaction with irradiation, physiologic mechanisms, and effects of hypertherrnia on microvasculature of tumors as well, as basic principles of physics and instrumentation of hyperthermia.key words: cancer-hyperthermia-radiation therapy-thermobiology-thermometry